Potential Nitrification and Nitrogen Mineral of Soil in Coffee Agroforestry System with Various Shading Trees - Purwanto .; Eko Handayanto; Didik Suprayogo; John Bako Baon; Kurniatun Hairiah (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2007)
The role of shading trees in coffee farms has been well understood to establish suitable condition for the growth of coffee trees, on the other hand their role in nitrogen cycle in coffee farming is not yet well understood. The objectives of this study are to investigate the influence of various legume shading trees on the concentration of soil mineral N (N-NH4 + and N-NO3-), potential nitrification and to study the controlling factors of nitrification under field conditions. This field explorative research was carried out in Sumberjaya, West Lampung. Twelve observation plots covered four land use systems (LUS), i.e. 1) Coffee agroforestry with Gliricidiasepium as shade trees; 2) Coffee agroforestry with Gliricidiaas shade trees and Arachis pintoias cover crops; 3)Coffee agroforestry with Paraserianthes falcataria as shade trees; and 4) Mixed/multistrata coffee agroforestry with Gliricidiaand other fruit crops as shade trees. Measurements of soil mineral-N concentration were carried out every three weeks for three months. Results showed that shade tree species in coffee agroforestry significantly affected concentrations of soil NH4 +, NO3- and potential nitrification. Mixed coffee agroforestry had the highest NH4+/N-mineral ratio (7.16%) and the lowest potential nitrification (0.13 mg NO2-kg-1 hour -1 ) compared to other coffee agroforestry systems using single species of leguminous shade trees. Ratio of NH4 + /N-mineral increased 0.8—21% while potential nitrification decreased 55—79% in mixed coffee agroforestry compared to coffee agroforestry with Gliricidia or P. falcatariaas shade trees. Coffee agroforestry with P. falcatariaas shade trees had potential nitrification 53% lower and ratio of NH4 + /N-mineral concentration 20% higher than that with Gliricidia. Coffee agroforestry with P. falcataria as shade trees also had organic C content 17% higher, total N 40% higher, available P 112% higher than that with Gliricidia. The presence of A. pintoiin coffee agroforestry with Gliricidiareduced 56% potential nitrification but increased 19.3% of NH4+/N-mineral concentration. The low soil potential nitrification in the mixed coffee agroforestry had close relationship with the high content of soil organic matter. Key words : Nitrogen-mineral, nitrification, shading trees, agroforestry, Coffea canephora, nitrate, organic matter, intercropping,Gliricidia sepium, Arachis pintoi, Paraserianthes falcataria.